1995
DOI: 10.1046/j.1523-1739.1995.09040806.x
|View full text |Cite
|
Sign up to set email alerts
|

Life History and Conservation of Totoaba macdonaldi

Abstract: We conducted a literature review on the biology, ecology, fishery, and protection of totoaba (Totoaba macdonaldi), an endemic, threatened fish of the Gulf of Calfornia, Mexico. Reinterpretation and integration of published and unpublished information enabled us to confirm and estimate specific biological parameters of the totooba, make hypothetical constructs of its life history, and to propose ideas for its preservation. In specific, we found (1) that the mean age of first reproduction of male and female toto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
1
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(124 citation statements)
references
References 5 publications
7
108
1
8
Order By: Relevance
“…The Gulf croaker, Micropogonias megalops, represents almost 27% of the total fish capture in the Upper Gulf of California (Aragón-Noriega et al 2009). The totoaba, Totoaba macdonaldi, supported one of the most important fisheries in the region; nevertheless, uncontrolled fisheries and the decrease of Colorado River flow and thus spawning, breeding, and reproduction of this species brought this fishery to collapse (Cisneros-Mata et al 1995). Currently, the totoaba is included in NOM-059-SEMARNAT-2010 regulation in the category of risk of extinct, and as Critically Endangered by the IUCN red list of threatened Species.…”
Section: Discussionmentioning
confidence: 99%
“…The Gulf croaker, Micropogonias megalops, represents almost 27% of the total fish capture in the Upper Gulf of California (Aragón-Noriega et al 2009). The totoaba, Totoaba macdonaldi, supported one of the most important fisheries in the region; nevertheless, uncontrolled fisheries and the decrease of Colorado River flow and thus spawning, breeding, and reproduction of this species brought this fishery to collapse (Cisneros-Mata et al 1995). Currently, the totoaba is included in NOM-059-SEMARNAT-2010 regulation in the category of risk of extinct, and as Critically Endangered by the IUCN red list of threatened Species.…”
Section: Discussionmentioning
confidence: 99%
“…Like many sciaenid fish, totoaba form large spawning aggregations at the water surface (Erisman et al 2010). Despite limited fishing capacity at that time, focused effort on spawning grounds increased catches from 296 tonnes in 1932 to 2286 tonnes in 1942 (Cisneros-Mata et al 1995a). New cotton and nylon nets and motorized boats in the 1940s and 1950s allowed fishers to haul entire spawning aggregations of totoaba (Bahre et al 2000), followed by the start of industrialized shrimp trawl operations which caught juvenile totoaba (machorros) incidentally.…”
Section: Preindustrial Fisheries and First Scientific Studies (1900-1mentioning
confidence: 99%
“…As the fishing sector struggled, fisheries scientists remained concerned about the totoaba population (Cisneros-Mata et al 1995a) while conservation groups (mostly U.S.-based) dedicated efforts to vaquita protection (McGuire and Valdez-Gardea 1997). Despite high uncertainty regarding population status or bycatch rates, vaquita was perceived by conservation advocates and scientists as a victim of lax environmental policy in Mexican fisheries and management (Fleischer and Pérez-Cortés 1996), a negative for NAFTA discussions.…”
Section: Industrial Fisheries Science and Conservation Advocacy (19mentioning
confidence: 99%
“…Historic sources of information included publications from several authors who reported historical data from the study region (i.e., Smith 1954;Malkin 1962;Cruz-Acosta 1979;Chenaut 1985;Felger and Moser 1985;Cisneros-Mata et al 1995;Bahre et al 2000;Bowen 2000;Basurto 2006). Recent sources of information were obtained through research efforts carried out by the authors of this study between 1995 and 2010, some of which have been published elsewhere (i.e., Bourillón 2002;Basurto 2005Basurto , 2008Basurto and Coleman 2010;Moreno et al 2005a, b;Cinti et al 2010a, b).…”
Section: Sources Of Informationmentioning
confidence: 99%